The Dirty Dozen - Nathanson, E. M. (London Cassell, 2002)
Twelve bearded, filthy GIs wait behind barbed wire, prisoners of their own army. Murderers, thieves, rapists, they wait to be sentenced to death or hard labour for life. They are the damned of the American Army. But at the last moment they are offered the opportunity of salvation: a mission just before D-Day. The chances of their getting away with it are about one in a million, but the damned don't care, and certainly don't count chances...
The story of a daring mission carried out by 12 army convicts, made famous by the film of the same name.
Keywords: World War (1939-1945) -- Prisoners -- Europe -- Americans -- Criminals -- United States